Scrutinizing the issues and challenges faced by postgraduate students: an effort to design specific programs to inculcate research culture / Posiah Mohd Isa and Yarina Ahmad - Mohd Isa, Posiah; Ahmad, Yarina (Journal of Administrative Science, 2018)
This paper presents issues and challenges faced by postgraduate research students who are enrolled in Master and Ph.D programs at the Faculty of Administrative Science & Policy Studies (FSPPP), Universiti Teknologi MARA, Selangor. The aim of this study is to explore students’ feedback and evaluation pertaining to their research progress, issues and challenges which lead to the implementation and construction of a specific program to support them in their research work. A qualitative approach using verbal and written interviews involving 16 research students was undertaken within a two-month period (October – November 2015) and their feedback was analyzed. The findings of this study reveal that more than half of the respondents indicated that ‘academic writing’ is their main issue and challenge throughout their period of study. The respondents claimed that they have difficulties in conveying their ideas into writing, restructuring sentences, building research arguments and lack of writing skills. Aside from academic writing, the respondents stated that ‘individual problems’, ‘personal problems’, ‘research method and techniques’ and ‘supervision’ are among the main issues and challenges that they encounter during their study. Further, the respondents provided suggestions and expectations to the faculty to assist them in their research. Following the inquiry on issues and challenges as well as suggestions, the faculty has taken a number of initiatives to support the research students. One of the remarkable initiatives is the implementation of the Graduate Researches in Print (GRiP) program to assist students in academic writing with an effective support group among their peers. The faculty has also implemented a number of workshops and seminars at the faculty level. The research students were strongly encouraged to attend programs, seminars and workshops organized by the Institute of Graduate Study (IGS), libraries and others. This study concludes that exploring students’ feedback on the issues and challenges as well as their suggestions and expectations is an effective way to design and implement initiatives and programs to support and assist them in their research journey. This can be considered as one of the best initiatives taken by the faculty to support research students, boost research culture and continuously encourage students to produce sound and quality research.